Management of Benign Prostatic Hypertrophy-Related Urinary Retention: Current Trends and Perspectives - Stamatiou, Konstantinos (Urology Journal, 2009)
The failure of prostate-directed treatment modalities to help all men or all symptoms has questioned the longstanding assumption that the prostate is at the root of all male urinary symptoms, and a correlation between urinary bladder function and prostate pathology has been recognized. Now, it is widely recognized that bladder dysfunction plays a role in some, if not most, of the benign prostatic hyperplasia-related symptoms and signs, and recent studies have suggested that pharmacotherapies that target the bladder, such as antimuscarinics, may improve storage urinary symptoms. Indeed, the current mainstays of overactive bladder syndrome pharmacotherapy are antimuscarinic agents with mixed actions, including musculotropic (calcium antagonistic) activity. Moreover, the combination therapy with alpha blocker and antimuscarinic agents is now suggested when bladder outlet obstruction related to benign prostatic hyperplasia coexists with overactive bladder symptoms. Combinational treatment, targeting to both decrease resistance to urine outflow through the prostatic urethra and increase bladder smooth muscle, may improve the bladder outlet surgery success rate, and perhaps it might reinforce the need to offer an additional trial without catheter in patients with benign prostatic hyperplasia who are likely to suffer from detrusor hypocontractivity. Currently, no clinical trial supporting the use of parasympathomimetic drugs in those with poor voiding and longstanding symptomatic benign prostatic hyperplasia exists in the literature; however, experimental studies present promising results.